The theory and its reflection Research about the theory of Architecture - asaad Yacoob Yacoob; Aday abas Abood (Iraqi Journal of Architecture and Planning, 2009)
The theoretical side is very important in Architecture because the Architecture in one of itsannouncements is just material acumilate which reflects a thoughtfut dimension to know moreabout effect and affect, we have to make clear the theoretical sides that reflects on and reflectsfrom it according to that theoretical dimension which takes it effects and its role in definingmore clear the image of Architecture in future. we have to explain exchanged effects andaffects between the Architecture and the theoretical side in the frame of a completedimensions for both ofthem the material and the theorical'Taking cure with the period differs ingrates and at last the thoughts results from accordingto the angles of analyzing and measuring. Adding to that what results from it and the effectthat wasleft on. All points on the importance and the effict of globalization depending on thesize of effection and its type which is actually left because it is expected that it will have itsactive role in creating the image skekage ofthe future the research us the principles oftheexplanation of this theory and its reflections on the Architecture and this refers to thedescriptions of the image of architecture in the future depending on its affects on it' Sowehave to make clear the gateral sides first of all then to make clear its special dimensionswhich provide basic information that make clear the type of data or its capacity ofbeingcrystalanditreflectsontheArchitecture,lightenedwiththedesignedpoleprocessanddescribing its effects on architecture and what crystallize the image of response direction forthis theory.